Diagnostic-driven management of invasive fungal disease in hematology in the era of prophylaxis and resistance emergence: Dutch courage?. (10th July 2019) - de Kort, E A; Maertens, J; Verweij, P E; Rijnders, B J A; Blijlevens, N M A
Abstract: Patients receiving intensive anti-leukemic treatment or recipients of allogeneic hematopoietic stem cell transplantation (HSCT) are prone to develop invasive fungal disease caused by both Aspergillus and non- Aspergillus moulds. Overall mortality following invasive mould disease (IMD) is high; adequate and timely antifungal treatment seems to ameliorate the outcome, yet early diagnosis in the haematological patient remains a challenge for most clinicians. Prophylaxis and the empiric addition of antifungal therapy to neutropaenic patients with fever persisting or recurring during broad-spectrum antibiotic treatment is therefore standard of care in many institutions. However, aside from the potential for overtreatment and important side effects, the emergence of resistance to medical triazoles in Aspergillus fumigatus poses a risk for inadequate initial treatment. Initial voriconazole therapy in patients with azole-resistant invasive aspergillosis was recently shown to be associated with a 23% increased mortality rate compared to the patients with azole-susceptible infection, despite changing to appropriate antifungal therapy once resistance was detected. Moreover, fever is not always present with IMD; therefore, cases may be missed when relying solely on this symptom for starting diagnostic procedures and antifungal treatment. At our institution, a diagnostic-driven treatment approach for IMD was implemented relying on clinical but also laboratory markers to start antifungal treatment. We describe the basis and clinical implementation of our diagnostic-driven approach in this review.